Telaah Konseptual Urgensi Tertanamnya Roh Jihad Seorang Pemimpin Pendidikan Terhadap Suksesnya Pendidikan Agama Islam - Nur Rofiq; Sigit Tri Utomo (Al-Idaroh: Jurnal Studi Manajemen Pendidikan Islam, 2019)
The phenomenon of moral decline and the humanitarian crisis is now rampant and is happening everywhere. The act is not only done by teenagers, but by some parents and even leaders. This can be seen by the proliferation of corruption, the association of free sex, drugs, the spread of news about sheepfighting and hatred and hoax news that are very disturbing to the public. Even radical movements in the name of religion and ethnicity began to flourish. The purpose of this study is to unravel the theme of the urgency of the spirit of the leadership of jihad embedded in the success of education because education leaders now face very heavy challenges in the success of education. The research method used in the research is the type of library research. Based on the results of the conceptual study the urgency of the spirit of the jihad of a leader towards the success of education is found that a leader in his heart implanted the spirit of jihad for the success of education, then a leader will devote all his abilities seriously in doing something in good totality concerning life, emotions, energy, mind and knowledge and time and place for the success of education. This shows that the ideal education leader is a leader who has leadership talents who are strong, responsible and have a spirit of great jihad in carrying out his leadership duties, and still maintain noble character in his own personality.